Exploring the clinical efficacy of a self‐made acne prescription based on high‐throughput sequencing. (4th June 2022) - Wang, Liangyi; Wu, Jingdong; Zhang, Xiaoqing; Gu, Wei; Han, Xiaoqing
Abstract: Background: We used high‐throughput sequencing on skin microbial flora to assess the effectiveness of an acne prescription to formulate evidence for clinical decision‐making. Methods: We randomized 20 outpatients into two groups. The treatment group was given the acne formula orally. The control group took capsules of the Chinese patent medicine Qingre Anchuang. Both groups used a chloramphenicol tincture externally. After 14 days of treatment, we collected their skin samples and extracted the deoxyribonucleic acid for analysis. Results: Forty samples were sequenced in this experiment, and of these, 1865 operational taxonomic units were obtained, belonging to 736 genera and 853 strains of 34 phyla. By alpha and beta diversity analysis, the abundance of microbial species in both the experimental and control groups before treatment was higher than after treatment, indicating the intervention drugs in this experiment had a bacteriostatic effect. Through the analysis of variance, we found that Subdoligranulum, Bifidobacterium, Bacteroides, and Akkermansia displayed large changes during the treatment. According to the linear discriminant analysis effect size, we discovered the bacteria groups with the greatest changes in the control group after treatment were Firmicutes, Clostridia, Proteobacteria, and Gammaproteobacteria. The flora of the experimental group before and after treatment were Corynebacteriaceae, Corynebacteriales, Cutibacterium, Propionibacteriales, Propionibacteriaceae, and Actinobacteria . Conclusion: The acne prescription had a reliable intervention effect on some epidermal microbial flora of patients with acne vulgaris and could inhibit the growth of acne‐related microbial flora, such as Propionibacterium .